COMMODIFICATION OF RELIGION AND THE EFFECT OF GLOBALIZATION ON ISLAMIC RELIGIOUS VALUES - Ade Afriansyah; Adinda Aulia Rahmah (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
This article discusses the influence of globalization on the values of Islam. Globalization is a phenomenon that brings about social changes in society. Islam, as a universal religion, has a significant impact on the social changes that occur due to globalization. This article outlines the positive and negative effects of globalization on Islam and emphasizes the importance of moderation in dealing with these changes. The research is based on many controversies that have arisen in the context of globalization, with a focus on the position of Islam in the global world. Its aim is to provide insight into the position of Islam on the global stage through a qualitative descriptive approach. The article also asserts that Islam remains relevant in facing the challenges of our times, especially in the era of globalization. The positive impacts of globalization include technological advancements and easier access to knowledge, while the negative impacts involve the erosion of ethics, morals, and lifestyles due to the influence of Western culture brought by globalization. The article also highlights fundamental differences in Islam that may lead to conflicts in dealing with globalization. Finally, the article raises questions about how a Muslim should respond to globalization that may not always align with Islamic principles.